EXPLORING TRI-VALUED LOGIC FOR VEDANTIC INTERPRETATION: A STUDY IN MULTI-VALUED LOGIC ALGEBRA - 1. Aniruddha Singhal , 2. C. Patvardhan (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
Background/Objectives: To examine how multi-valued logic aligns with Vedantic truth and enhances the understanding of paradoxes in mathematics, quantum mechanics, and logic. Methods/Statistical analysis: In this study, we will compare and contrast the core ideas of Vedantic philosophy with tri-valued logic, exploring their similarities and differences. We will then identify the limitations of binary logic by analyzing various paradoxes from literature, shedding light on its shortcomings. Finally, we aim to propose a conceptual framework for applying tri-valued logic, drawing insights from our comparative analysis. Findings: Tri-Valued Logic Compatibility: Our analysis reveals that Graham Priest’s paraconsistent logic aligns closely with Vedantic concepts, particularly the notion of Mithya, providing a robust framework to interpret self-referential paradoxes and contradictions. Resolution of Paradoxes: The integration of tri-valued logic and Vedantic philosophy offers a unique perspective on classical paradoxes, such as the Liar Paradox and Zeno’s Paradoxes, suggesting that contradictions can coexist and lead to deeper understanding rather than logical dead ends. Legal Implications: This approach highlights the limitations of binary categorizations in legal contexts, allowing for a nuanced interpretation of laws and ethical dilemmas, which is not extensively covered in existing frameworks. Cultural Relevance: Our findings underscore the importance of Eastern philosophical perspectives in contemporary logical discourse, suggesting a paradigm shift that challenges traditional Western logic. Novelty/Applications: This research uniquely integrates tri-valued logic with Vedantic philosophy, enhancing understanding of paradoxes and offering innovative frameworks for ethical AI decision-making and nuanced legal interpretations.